BEYOND THE DIGITAL DIVIDE: FRUGAL PEDAGOGY AND TEACHER RESILIENCE IN MATHEMATICS EDUCATION - Rifka Nadia (RADJA PUBLIKA, 2025)
This qualitative study investigates the pedagogical practices and professional resilience of mathematics teachers in severely under-resourced junior high schools in the interior of North Aceh, Indonesia. In a context defined by a chronic lack of infrastructure, teaching aids, and internet connectivity, the dominant techno-centric paradigm of mathematics education is rendered irrelevant. Through semi-structured interviews with seven teachers, the research employed thematic analysis to explore how effective instruction is conceived and enacted within systemic constraints. The findings reveal a sophisticated model of context-embedded frugal pedagogy, characterized by three interrelated themes: the creative improvisation of teaching materials from the local socio-cultural environment; the reconfiguration of the teacher's role into a holistic motivator and cultural broker; and the cultivation of resilience through a deep sense of purpose and informal professional communities. The study concludes that in low-resource settings, pedagogical quality is principle-driven rather than technology-dependent, with the teacher-student relationship serving as the primary affordance for learning. This research challenges deficit narratives by demonstrating how constraints can catalyze pedagogical innovation and robust professional identity. It advocates for the inclusion of frugal pedagogy in teacher training and proposes a more pluralistic, context-sensitive understanding of effective mathematics education.